Psychological Distress Phenomena in Young Adults Due to Toxic Family Relationships - Nurwahyuni Nasir; Sandra Adetya; Fathana Gina (Insight School Academy, 2024)
Introduction to The Problem: Interpersonal relationships within families represent a crucial aspect of individual development, particularly during early adulthood. However, not all family relationships are harmonious; some individuals face toxic relationship dynamics. Toxic relationships in families refer to relationships characterized by harmful interaction patterns, such as excessive control, emotional manipulation, lack of support, and abusive behavior. Studies indicate that toxic family relationships can affect mental health, increasing the risk of depression, anxiety, and post-traumatic stress disorder. Purpose: This phenomenological study aims to explore the in-depth experiences of individuals who have encountered such relationships and how they interpret these dynamics. Design/methods/approach: A descriptive phenomenological approach was used to understand participants' subjective experiences as they are, without additional interpretation from the researcher. The participant characteristics include young adults aged 18 to 29 years, who are capable of reflecting on their experiences when near or together with their parents. This study employed a questionnaire for data collection. For the psychological distress variable, The Hopkins Symptom Checklist (HSCL)-25 was used, consisting of 2 dimensions: anxiety symptoms (items 110) and depression symptoms (items 11-15). Findings: The research results indicate that the majority of females aged 18-20 years tend to experience psychological distress, marked by high levels of anxiety and depression. This phenomenon can be linked to toxic relationships with parents, often characterized by prolonged conflict, poor communication, manipulative behavior, or emotional and physical abuse, thus creating an unstable and high-pressure environment.